Uma caracterização do toro com curvatura média constante em formas espaciais - Sousa, Edno dos Santos (2008)
In this dissertation we study the geometry of surfaces isometrically immersed in a 3-dimensional space form imposing some conditions on its mean and gaussian curvature. If the gaussian curvature is non-positive we prove that the surface is a sphere, a product of circles or a cylinder. It is also proved that if a surface locally H-deformable is a torus; then it mean curvature is constant.